Arquitectos argentinos en el mundo : diálogos y proyectos - Grossman, Luis J.; Casoy, Daniel O. (Buenos Aires : Photon Press, 2006)
Diálogos con los arquitectos: Emilio Ambasz- Mario Corea - César Pelli - Eduardo Elkouss - Carlos Prus - Ignacio Dahl Rocha - Juan Pfeifer - Eduardo Catalano - Rafael Viñoly -- Proyectos: Banco de Ojos - Torres Monumento / Emilio Ambasz ; Estadio de Atletismo de Sabadell - Nuevo Hospital de Mollet / Mario Corea y Lluís Moran ; Centro de Ciencias y Exploración de Connecticut - Centro Bokde Grandes Eventos / Cesar Pelli, Fred Clarke y Rafael Pelli - Museo Escuela del Vino - Centro Comercial Mosaico / Eduardo Elkouss ; Plaza del Mercado - Viviendas en Avenida en Shai Agnon / Carlos Prus y Aharón Silberstein ; Museo de Bellas Artes de Lausana - Clínica La Prairie / Ignacio Dahl Rocha y Jacques Richter ; Marina Arauco Mall - Reforma del Centro Comercial Moraleja Green / Pfeifer, Zurdo, Di Clérico, Pfeifer y Qüesta ; Jardín de la Paz -Casa Raleigh / Eduardo Catalano ; Escuela de Negocios de la Universidad de Chicago - Museo de Arte Nasher de la Universidad de Dulke / Rafael Viñoly
Keywords: ARQUITECTOS; BIOGRAFIAS; ARGENTINA; DIALOGOS; PROYECTOS; AMBASZ, EMILIO; COREA, MARIO; PELLI, CESAR; ELKOUSS, EDUARDO; PRUSS,CARLOS; DAHL ROCHA, IGNACIO; PFEIFER, JUAN; CATALANO, EDUARDO; VIÑOLY, RAFAEL